Parameter Genetik dan Daya Gabung Hasil dan Komponen Hasil Jagung pada Tiga Taraf Pemupukan N - Priyanto, Slamet Bambang; Efendi, Roy; Azrai, Muhammad (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2021)
Low maize yields due to low nitrogen generally occur on marginal land. Maize development in Indonesia is directed at marginal land due to limited fertile land, especially in other lands in Indonesia besides Java. Therefore, the assembly of low N tolerant maize varieties plays an important role in increasing production on marginal land. Therefore, the improvement of low N tolerant hybrid maize was required. Information on the combining ability of inbred lines was important in the hybrid maize breeding program. This research aims were to determine genetic parameters, general combining ability, specific combining ability of maize lines and at three levels of N fertilization. This research was conducted at the Bajeng Experimental farm South Sulawesi from August to November 2019. The research was arranged in a split-plot design with two replications. The main plots were three nitrogen levels i.e. 0 kg N/ha, 100 kg N/ha, 200 kg N/ha and the subplots were 36 hybrids formed from a half diallel cross and its parents. The results showed that compared to yield at 200 kg N/ha, yield at 100 kg N/ha and 0 kg N/ha reduced 18,80% and 38,69% respectively. ear number, ear weight, shelling percentage and number of seeds per row were controlled by non-additive genes, while moisture content, 100 seeds weight, ear length and number of rows per ear were controlled by additives gene. Lines AVLN 118-7 and AVLN 83-2 have good GCA for yield grain overall levels of fertilization. Crosses AVLN 83-2/AVLN 124-4, AVLN 83-2/AVLN 32-8, and AVLN 122-2/AVLN 124-9 have the good combining ability under both low and high N conditions. They could be used to develop low N tolerant varieties.